Validation of the Slovenian versions of Child and Youth Resilience Measure-12 and Brief Resilience Scale among youth - Smrke, Urška; Rehberger, Ana; Močnik, Sara; Špes, Tanja; Mlakar, Izidor; Plohl, Nejc (Frontiers in Psychology, 2025)
IntroductionResilience is the ability to adapt positively in the face of adversity, trauma, or significant stress and is a vital component of maintaining mental health and well-being. It is particularly shaped in young adulthood by navigating unique stressors, such as changes in living arrangements, relationships, and education. However, much of the existing research focuses on children or older adults, leaving a gap in our knowledge regarding resilience in young adulthood. Moreover, the existing resilience scales are seldom validated outside of English-speaking contexts. With this paper, we turn attention to validating two resilience measures, Child and Youth Resilience Measure-12 (CYRM-12) and Brief Resilience Scale (BRS), in Slovenian language, using a sample of young adults.MethodWe administered a survey among 330 young individuals (18–24 years) from Slovenia. Next to the central questionnaires, we also measured resilience with another scale, along with coping strategies, anxiety, depression, and quality of life.ResultsFor both resilience scales, one-factor structures fitted the data well and both scales demonstrated good internal consistency. CYRM-12 and BRS showed positive associations with another resilience scale and adaptive coping strategies, negative associations with anxiety, depression, and maladaptive coping strategies, and a unique contribution to predicting quality of life (with CYRM-12 demonstrating somewhat greater predictive value for quality of life than BRS), pointing to good convergent, discriminant, and incremental validity, respectively.DiscussionThe results of our study suggest that CYRM-12 and BRS are both sufficiently reliable and valid for use among Slovenian young adults, with slightly stronger evidence supporting the validity of CYRM-12 compared to BRS.